Entrepreneurs in rural areas: Challenges and opportunities - Md Isa, Filzah; Othman, Siti Norezam; Mohd Nor, Nor Azila; Yahya, Mohd Azlan; Salahuddin, Norkhazzaina (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
Small and medium enterprises (SMEs) in Malaysia play an important role in supporting new economic model that focuses on innovation and creative industry. A review of the relevant small business literature, however, revealed that there are limited studies attempting to investigate the issue of entrepreneurs in rural areas. This article attempts to study the role, contribution problems, and constraints related to the rural entrepreneurs, which may affect their operations, survival, growth, stability, and profitability. Using questionnaire and structured interview, the data for this study was collected from 700 rural entrepreneurs who had attended training and development programs conducted by Cooperative and Entrepreneur Development Institute(CEDI) UUM from 2006 until 2008. Findings of the study indicate that rural entrepreneurs are motivated by necessity-driven factors and not opportunity-driven factor when starting up their business. Nevertheless, the common problems and constraints that are faced by rural entrepreneurs ranging from lack of access to capital support scheme up to the outdated business vision and value. The results of the study would help authority to improve rural entrepreneurs program conducted by government agencies and policy related to entrepreneurs.